Colchicine can keep the viability of bacteria in mastitic milk by preventing leukocyte phagocytosis in dairy cow and goat - Hisaeda, Keiichi; Hirano, Masato; Suzuki, Naoki; Isobe, Naoki (Frontiers in Veterinary Science, 2024)
Despite the occurrence of mastitis, no bacteria were detected in any of the milk samples after culture. This is partially because the neutrophils present in milk phagocytose bacteria during milk preservation. In this study, we investigated whether colchicine inhibited the decrease in viable bacteria in milk by suppressing phagocytosis during preservation. The number of viable bacteria decreased when cow milk was preserved for 5 h. However, the addition of 0.1 and 1% colchicine significantly increased the number of viable bacteria (p < 0.05). The percentage of culture-negative cow’s milk increased more than two-fold after 5 h compared to that at 0 h of preservation, however this percentage was significantly reduced by the addition of colchicine (p < 0.05). When goat milk with mastitis was incubated with bacteria (Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus), the percentage of phagocytosed neutrophils decreased significantly with the addition of colchicine (p < 0.05). These results indicate that colchicine suppressed the decrease in the number of viable bacteria by preventing neutrophil phagocytosis during milk preservation. These findings may help in the identification of mastitis-causing bacteria and the selection of antibiotics for the treatment of mastitis.